Epidemiology and risk factors for thrombosis in children and newborns: systematic evaluation and meta-analysis - Shuang Song; Zhuowei Li; Guozhen Zhao; Xintong Li; Runying Wang; Bo Li; Qingquan Liu (BMC, 2023)
Abstract Background Thrombosis is a serious condition in children and neonates. However, the risk factors for thrombosis have not been conclusively determined. This study aimed to identify the risk factors for thrombosis in children and neonates in Intensive Care Unit (ICU) through a meta-analysis to better guide clinical treatment. Methods A systematic search of electronic databases (PubMed, Embase, Cochrane Library, WOS, CNKI, Wanfang, VIP) was conducted to retrieve studies from creation on 23 May 2022. Data on the year of publication, study design, country of origin, number of patients/controls, ethnicity, and type of thrombus were extracted. The publication bias and heterogeneity between studies were assessed, and pooled odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using fixed or random effects models. Results A total of 18 studies met the inclusion criteria. The incidence of thrombosis in children was 2% per year (95% CI 1%-2%, P < 0.01). Infection and sepsis (OR = 1.95, P < 0.01), CVC (OR = 3.66, [95%CL 1.78-7.51], P < 0.01), mechanical ventilation (OR = 2.1, [95%CL1.47-3.01], P < 0.01), surgery (OR = 2.25, [95%CL1.2-4.22], P < 0.01), respiratory distress (OR = 1.39, [95%CL0.42-4.63], P < 0.01), ethnicities (OR = 0.88, [95%CL 0.79-0.98], P = 0.78), gestational age (OR = 1.5, [95%CL1.34-1.68], P = 0.65)were identified as risk factors for thrombosis. Conclusions This meta-analysis suggests that CVC, Surgery, mechanical ventilation, Infection/sepsis, gestational age, Respiratory distress, and different ethnicities are risk factors for thrombosis in children and neonates in ICU. These findings may help clinicians to identify high-risk patients and develop appropriate prevention strategies. Trial registration PROSPERO (CRD 42022333449).